Le prieuré Sainte-Marguerite dit de Monaqueville - Bavay, Jeannine (Vikland: la revue du Cotentin, 2015)
Keywords: monaqueville

Terrasini, completato il restauro della chiesa di San Cataldo - Catalano, Maria Carola (Palermo Today, 2015)
Keywords: terrasini

On the Life of Those Who Dwell in Enclosure - Scot, Adam (Cistercian Studies Quarterly, 2015)
The article presents a sermon about Mary Magdalene by Anglo-Scottish theologian Adam Scot, also known as Adam of Dryburgh or Adam the Carthusian, dedicated to the Canons Regular of Prémontré. The sermon considers how Mary reminds about the singular privilege of those who live in enclosure within God, and of those who come near the Lord himself and cling to him tenaciously. It also looks at what the Gospel say about Mary, about anointing Jesus' feet with a pound of costly perfume.
Publisher: Cistercian Studies Quarterly
Keywords: 👤 adam of dryburgh

Stained Glass from the Corcoran Gallery to Return to Park Abbey - Shortell, Ellen M. (Vidimus, 2015)
Keywords: park

'Clothing for the Soul Divine': Burials at the Tomb of St Ninian: Excavations at Whithorn Priory, 1957-67 - Lowe, Christopher E. (Historic Environment Scotland, 2015)
Whithorn, known as Scotland's Cradle of Christianity, is unique as a centre of worship, administration, and ultimately pilgrimage, dating back to the 5th century.The work carried out at Whithorn Priory by Roy Ritchie in the late 1950s and 1960s is the only modern excavation campaign to focus on the high status burials near the high altar of a major Scottish medieval church. Remains of earlier graves, as well as structures now recognised as parts of the extended medieval cathedral church, were uncovered. Among the uppermost level of graves are those that belong to a number of Whithorn's bishops, some of whom are tentatively named.This volume details the results of historical and scientific analysis of the remains of the bishops - who they were and where they came from, together with the circumstances of their deaths and burial. Many of these graves were richly furnished - including altar plate and the famous Whithorn crozier - and the full assemblage of artefacts from the excavation is published here for the first time. This publication also resolves, once and for all, the nature and date of the earliest graves that were identified at the base of the trench. The story of one of Scotland's most important 'lost excavations' can now be told.
Google-Books-ID: JkWNRAAACAAJ
Keywords: whithorn

Ancient abbey dig set to resume at Leiston - Potter, Tom (The East Anglian Daily Times, 2015)
Keywords: leiston

Nacht van Geschiedenis belicht 864 jaar Hof te Kattem (VILT, 2015)
Keywords: kattem

La redécouverte de l’abbaye d’Abbecourt (Orgeval, Yvelines) (La lettre d'aristeas, 2015)
Keywords: abbecourt

Kanonie premonstrátů Teplá: Národní kulturní památka (2015)
Keywords: teplá

Kloster Speinshart Panorama Rundgang (2015)

St. Norbert and His Order (Mediatrix Press, 2015)
Keywords: 👤 norbert of xanten; 📚 premonstratensian (general)

Kurze Geschichte des Klosters Maria Engelport von 1220 bis heute - Ackermann, Stephan; Pies, Norbert J. (100 Jahre Lourdesgrotte Kloster Maria Engelport : Festschrift, 2015)
Keywords: engelport

El monasterio premonstratense de Santa María de la Vid (Burgos). Siglos XII-XV - Angulo Fuertes, María Teresa (Universidad Nacional de Educación a Distancia, 2015)
Keywords: la vid

Premontrei prépostság feltárása Bárdudvarnokon - Aradi, Csilla M.; Molnár, István (Fiatal Középkoros Régészek VI. Konferenciájának Tanulmánykötete, 2015)
Keywords: kaposfő

Discours d'ouverture: les Prémontrés et Beauport - Ardura, Bernard (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Deux décennies de travaux et découvertes à l'abbaye de Beauport (1992-2012) - Ballini, Annie-Claude (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Neues zum Cappenberger Barbarossakopf - Balzer, Edeltraud (Westfalen, 2015)
Keywords: cappenberg

Lahonce (64), Abbaye : rapport de diagnostic - Béague, Nadine; Fabrice, Leroy (Inrap GSO, 2015)
Keywords: lahonce

Inventarien der Klöster Weidas und Münsterdreisen 1553 - Becker, Christa (Kaiserslauterer Jahrbuch für pfälzische Geschichte und Volkskunde, 2015)
Keywords: münsterdreisen

Une présence anglaise à Beauport, Le marbre de Purbeck XIIIe siècle - Beneult, Dominique (Les Cahiers de Beauport, 2015)
Keywords: beauport

Rīgas Doma viduslaiku arhitektūra un būvplastika eiropeisko analoģiju kontekstā - Bergholde, Agnese (Latvijas Māksalas akadēmijas Mākslas vēstures institūts, 2015)
Keywords: rīga

Die Eigenkirche der Grafen von Cappenberg als Urzelle des Klosters Ilbenstadt - Bewerunge, Norbert (Archiv für mittelrheinische Kirchengeschichte, 2015)
Keywords: ilbenstadt

Neue Forschungen zum Prämonstratenserstift Grobe auf der Indsel Usedom: Ausgrabungen am Wilhelmshofer Priesterkamp im Jahre 2010 - Biermann, Felix Paul (Bodendenkmalpflege in Mecklenburg-Vorpommern, 2015)
Keywords: grobe

Archäologische Forschungen am Prämonastratenserstift Belbuck bei Treptow an der Rega - Biermann, Felix Paul; Dworaczyk, Marek; Rebkowski, Marian (Baltische Studien, 2015)
Keywords: białoboki

Statuten mittelalterlicher Ordensgemeinschaften: Strategien normativer Stabilisierung mittels statutarischer Gesetzgebung am Beispiel der Zisterzienser, Prämonstratenser, Dominikaner und Franziskaner - Bitterlich, Markus (Technische Universität Dresden, 2015)
Keywords: ⚖️ chapters and statutes; 📚 premonstratensian (general)

Late Romanesque Convent Church of the Norbetine Sisters in Zwierzyniec in Cracow in the Light of Architectural Research from 2010-2011 - Bojes-Bialasik, Anna; Czechowicz, Jacek (Cihla a stavební keramika ve stredoveku a novoveku v mestské architekture strední Evropy, 2015)
Keywords: zwierzyniec

Die Siegel der mährischen Pramonstratenser als Quelle zur Geschichte der Zirkarie - Bolom-Kotari, Martina (Ordenshistoriographie in Mitteleuropa: Gestaltung und Wandlung des institutionalen und persönlichen Gedächtnisses in der frühen Neuzeit ; Referate der gleichnamigen Tagung in St. Pölten von 22. bis 23 September 2014, 2015)
Keywords: 🇨🇿 czechia (general)

O klobouku na pečetích zábrdovických premonstrátů - Bolom-Kotari, Martina (Archivum amicus historici est : sborník příspěvků k životnímu jubileu Hany Jordánkové, 2015)
Keywords: zábrdovice

Het Norbertinessenklooster Sint-Gerlach te Houthem. 1200-1800 - Bosmans, J. (Zusterkloosters in de Premonstratenzer Orde, 2015)
Keywords: sint-gerlach

Les saints de Beauport - Bourgès, André-Yves (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Rothenkirchen, St. Maria: Prämonstratenserabtei: Rothenkircherhof, Stadt Kirchheimbolanden, Verbandsgemeinde Kirchheimbolanden, Donnersbergkreis - Burkhart, Ulrich; Werling, Michael (Pfälzisches Klosterlexikon, 2015)
Keywords: rothenkirchen

San Catauru: luogo della memoria. Identità di un Santo. Identità di una contrada, identità di una chiesa - Cavaretta, Irene; Cipriano, Margherita; Cardinale, Ino (Arti Grafiche Abbate, 2015)
Keywords: terrasini

La pierre à Beauport. Un polylithisme coloré - Chauris, Louis (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

La noblesse et Beauport au XIIIe siècle - Coativy, Yves (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

La blanche brebis, l'âne et le bouc: les prémontrés dans la littérature exemplaire au Moyen Âge - Debert, Aline (Actes officiels des 34e et 35e Colloques du Centre d'études et de recherches prémontrées : Sarthe, 2008, Lorraine 2009, 2015)
Keywords: 📚 premonstratensian (general)

Der Cappenberger Barbarossakopf und sein Reliquienkreuz - Dethlefs, Gerd (Westfalen, 2015)
Keywords: cappenberg

Heurts et malheurs d'une abbaye royale navarro-labourdine : Salbatore d'Urdazubi - Duvert, Mikel (Terres de Navarre, 2015)
Keywords: urdax

Die Prämonstratenserinnen im deutschen Sprachraum und ihr Verhältnis zu den geistlichen und weltlichen Herren - Ehlers-Kisseler, Ingrid (Analecta Praemonstratensia, 2015)
Keywords: 🇩🇪 germany (general)

Neuere Forschungen zur Entstehung und Entwicklung der Frauengemeinschaften im Prämonstratenserorden - Ehlers-Kisseler, Ingrid (Zusterkloosters in de Premonstratenzer Orde, 2015)
Keywords: 📚 premonstratensian (general)

Les Chartes de l'abbaye de Beauport des origines à 1305: analyse des données - Evans, Claude (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Histoires d'argent: emprunts et prêts dans les chartes de l'abbaye de Beauport - Evans, K. Paul (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Die Beziehungen zwischen dem Kloster Speinshart und den Markgrafen von Bayreuth - Fuchs, Bernhard (Archiv für die Geschichte von Oberfranken, 2015)
Keywords: speinshart

Erinnerungsstätte und Wahrzeichen. Geschichte und Nachleben des ehemaligen Prämonstratenserstifts St. Marien auf dem Harlungerberg in Brandenburg an der Havel - Gahlbeck, Christian (Die Mark Brandenburg unter den frühen Hohenzollern. Beiträge zur höfischen Kunst und Architektur im 15. Jahrhundert, 2015)
Keywords: brandenburg:st marien

Beauport: architecture, hiérarchie, circulations dans une abbaye prémontrée du XIIIe siècle - Gallet, Yves (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Beauport, le paradis perdu du chanoine Le Sage - Gicquel, Samuel (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Beauport: l'invention d'une histoire - Gondolle, Sophie (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Eine verschwundene Quaternionendarstellung im Kloster Schussenried - Graf, Klaus (Archivalia, 2015)
Keywords: schussenried

F. W. E. Roth und die Briefsammlung des Prämonstratensers Ulrich von Steinfeld - Graf, Klaus (Archivalia, 2015)
Keywords: steinfeld

Déplacer les morts à l'abbaye d'Ardenne. De la réduction de corps à la sépulture secondaire - Guillon, Mark (Déplacer les morts. Voyages, funérailles, manipulations, exhumations et réinhumations, 2015)
Keywords: ardenne

Die Innenrestaurierung der Propsteikirche St. Walburga in Werl: weitere Ergebnisse der Bauforschung - Halekotte, Theo (Werl gestern, heute, morgen. Ein Jahrbuch der Stadt Werl und des Neuen Heimat- und Geschichtsvereins Werl, 2015)
Keywords: werl

Un prémontré au purgatoire: le livre de prières d'Heinrich Österreicher. - Hamburger, Jeffrey F. (Art de l'enluminure, 2015)
Keywords: 📚 premonstratensian (general)

Willem II of Floris de Voogd? Vragen rond een grafmonument en een skelet in de Koorkerk te Middelburg - Henderikx, Peter A. (Bijdragen en mededelingen betreffende de geschiedenis der Nederlanden, 2015)
William II or Florence the Guardian?: Questions about a Tomb and a Skeleton in the Abbey Church at Middelburg Both William II, Count of Holland and Zeeland and King of the Holy Roman Empire (†1256, re-interred 1282) and his brother Florence the Guardian (†1258) are buried in the Norbertine abbey church in Middelburg. In 1817 a skeleton was found in a bricked up niche, along with the remains of a tombstone on which was carved a knightly figure whose shield bears the coat of arms of Holland. Based on the results of an examination of the bones by George J.R. Maat and his team (Leiden University Medical Centre), Henderikx takes it that the skeleton could be either that of the King of the Holy Roman Empire or of Florence the Guardian. Considering that the skeleton, burial space and tombstone formed a coherent whole, and the high-relief on the tombstone almost certainly does not refer to the King of Rome but to his brother, Henderikx concludes that the skeleton must be the earthly remains of Florence the Guardian.
Keywords: middelburg

La situation monastique de la Bretagne jusqu'en 1202, année de la fondation de l'abbaye prémontrée de Beauport - Hillion, Yannick (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Krajiny trí klášteru (Teplá, Chotešov, Vyšší Brod): nástin problematiky - Hlinomaz, Milan (Krajina jako antropologická cítanka, 2015)
Keywords: chotěšov; teplá

Die mittelalterliche Klosteranlage von Sankt Salvator am Steinkart. Eine Spurensuche - Huber, Markus T. (Landkreis Passau, Kulturreferat, 2015)
Keywords: griesbach

Antropologia i arqueologia dels enterraments de l'exterior de l'església de Bellpuig (Artà) - Inglada Grau, Helena; Prats Picó, Noemi; Cardona López, Francisca; Llinàs Riera, Maria; Vila Socias, Llorenç (Bolletí de la Societat Arqueològica Lul·liana, 2015)
Keywords: bellpuig de artá

Des chanoines prémontrés en Goëlo et dans l'ouest de la France - Jeanneau, Cédric (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: goëlo

L'abbaye de Beauport et son insertion en Goëlo: liens avec les autorités ecclésiastiques, appuis aristocratiques et stratégies domaniales - Jeanneau, Cédric (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport; goëlo

Une abbaye prémontrée en Bas-Poitou: Lieu-Dieu-en-Jard - Jeanneau, Cédric (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: lieu-dieu-en-jard

Medieval law and materiality: shipwrecks, finders and property on the Suffolk coast, ca. 1380-1410 - Johnson, Tom (American Historical Review, 2015)
Keywords: leiston

Die Bestattungen beim spätmittelalterlichen Prämonstratenserstift Grobe (Wilhelmshof) auf der Insel Usedom: Ergebnisse der anthropologischen Analysen - Jungklaus, Bettina (Bodendenkmalpflege in Mecklenburg-Vorpommern, 2015)
Keywords: grobe

Zur Namensgebung der Marienkirche Gelnhausen: Zusammenstellung der Bezeichnungen - Kappel, Hans-Henning (Gelnhäuser Geschichtsblätter, 2015)
Keywords: gelnhausen (marienkirche)

Kult świętych w średniowiecznym Nowym Sączy - Kazienko, Ewelina (Nasza Przeszłość. Studia z dziejów Kościoła i kultury katolickiej w Polsce, 2015)
Keywords: nowy sącz

Petersberg, St. Peter: aufgegebene Klostergründung, später Propstei der Prämonstratenserabtei Arnstein: Gemeinde Gau-Odernheim, Verbandsgemeinde Alzey-Land, Landkreis Alzey-Worms - Keddigkeit, Jürgen; Misamer, Julia; Untermann, Matthias (Pfälzisches Klosterlexikon, 2015)
Keywords: petersberg

Politické aspekty ikonografie nástěnných maleb v kapli sv. Michala v premonstrátském klášteře v Lelesu - Kolářová Takácsová, Kornélia (Obrazy uctívané, obdivované a interpretované: Sborník k 60. narozeninám profesora Jana Royta, 2015)
Politische Aspekte der Ikonographie der Wandgemälde in der Michaelskapelle des Prämonstratenserkloster in Leles
Num Pages: 520 Pp.
Keywords: leles

A leleszi premontreiek szalókai birtoklásának háttere - Kovács, Viktória (Történelmi Szemle, 2015)
[The Background to the Landowning of the Premonstratensians of Lelesz at Szalóka] Although the founding charter of the Holy Cross provostry at Lelesz (today Leles, Slovakia) from 1214, of dubious authenticity, has not survived in the original, one of its later transcriptions from 1334 lists among the grants made by bishop Boleslo of Vác in favor of the provostry a possession called Zolunta. The people of Zolunta are reported to have robbed Russian tradesmen, an act later proved by the tradesmen through ordeal in the church of Buda, whereupon Zolunta was adjudicated to them by court ispán (comes curialis) Egyed. The village was eventually bought by the bishop of Vác from the tradesmen for 82 marks. The possession in question has traditionally been identified in the research with Szalonta in the medieval county of Borsod (Hejőszalonta, Hungary). According to Ambrus Pleidell, however, the provostry owned Szalóka (Solovka, Ukraine), which was variously regarded as belonging to the counties of Bereg and Ung in the Middle Ages. In the course of various lawsuits in 1336, 1343 and 1378, the monastery proved its title to Szalóka in Bereg with the founding charter and its later transcriptions. It is likewise Szalóka that is recorded as a possession of the provostry by the tax register of 1550. In order to establish which possession was in fact owned by the monastery of Lelesz, the author examines the charters which have preserved the relevant part of the founding charter, as well as the medieval variants of the names of the two settlements and their history. Two among the three textual traditions of the founding charter (1214/1334/1342/1364/1406, 1214/1334, 1214/1362) contain variants of the toponym Szalonta, which thus probably figured in the charter of 1214 as well. In the summary transcriptions connected to the presentation of titles in lawsuits (1336, 1343, 1378) it is Szalóka which appears without exception. The forms of toponyms, while fairly similar to each other, certainly refer to different settlements. As for Szalonta, prior to 1319 it was owned by the Ákos kindred, and thereafter by Dózsa Debreceni, voevode of Transylvania – consequently, it surely did not belong to the monastery of Lelesz in the early 14th century. Szalóka, on the other hand, was owned in the first half of the 13th century by Artolf of the Aba kindred, from whom it was purchased by the son-in-law of ban Bánk called Simon. In 1270 it was in the possession of Mihály son of Endre of the Rosd kindred, and in 1285 in that of his widow and new husband, Jakab Lónyai. In a protest made before the chapter of Eger in 1302 the provost of Lelesz claimed that Szalóka belonged to his monastery. On the basis of this information, the most probable solution seems to be that, while the provostry had originally come into the possession of Szalonta by virtue of the founding charter, later in the Angevin period it used the document to prove its title to landowning at Szalóka. During the lawsuits, the monastery probably argued that the Zolunta/Zolounta figuring in the charters in fact referred to Szalóka in Bereg.
Keywords: leles

Deutsche Literatur des Mittelalters in Handschriften aus dem Kloster Weißenau - Kruse, Norbert (Ulm und Oberschwaben, 2015)
Keywords: weissenau

Het voormalige Norbertinessenklooster van Gempe ('s Hertogeneiland) in Sint-Joris-Winge - Lani, Stefan van (Zusterkloosters in de Premonstratenzer Orde, 2015)
Keywords: gempe

L'obituaire de l'abbaye de Beauport - Le Goff, Amandine (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Ermida do Paiva: Arquitetura e Escultura - Lopes Cunha, Cláudia Gonçalves (University of Porto, 2015)
Keywords: ermida do paiva

Ke stavu poznání stavebních dejin bý valého kláštera premonstrátek Rosa Coeli v Dolních Kounicích: Nález románského obytného objektu pod stavbou barokního konventu - Merta, David; Peška, Marek (Archaeologia historica, 2015)
[Zum Erkenntnisstand über die Baugeschichte des ehemaligen Prämonstratenserinnenklosters Rosa Coeli in Dolní Kounice]
Keywords: kounice

Majetkové spory zábrdovického kláštera v polovině 15. století - Mlateček, Karel (Vyškovský sborník : sborník Moravského zemského archivu v Brně, Státního okresního archivu Vyškov, 2015)
Keywords: zábrdovice

L'abbaye du Perray-Neuf - Présentation historique et architecturale - Moulin, Jacques (Actes officiels des 34e et 35e colloques du Centre d'Études et de Recherches Prémontrées, 2015)
Keywords: perray-neuf

Życie norbertanek żukowskich w wieku XV i na początku XVI stulecia - Możejko, Beata (Res Gestae, 2015)
Keywords: żukowo

Secessit clarissimi viri ... primogenitus – Fragment einer Grabinschrift in der Klosterkirche Hane - Müller, Gerald F. W. (Jahrbuch für das Land um den Donnersberg, 2015)
Keywords: hane

Meister Eckhart auf der Wartburg: Fundbericht anlässlich der Wiederentdeckung einer frühen Eckhart-Handschrift aus dem Prämonstratenserinnenstift Altenberg im Bestand der Wartburg-Stiftung - Nemes, Balázs J. (Wartburg-Jahrbuch, 2015)
Keywords: altenberg

Prämonstratensische Wege nach Rom: Die Papsturkunden der fränkischen und schwäbischen Stifte bis 1378 - Petersen, Stefan (Böhlau Verlag, 2015)
Keywords: 📚 premonstratensian (general)

Chronologie de l'abbaye du Perray-Neuf - Plouvier, Martine (Actes officiels des 34e et 35e colloques du Centre d'Études et de Recherches Prémontrées, 2015)
Keywords: perray-neuf

Destins croisés des abbayes prémontrées de l'ouest de la France Moyen Âge. La place de Beauport dans le réseau médiéval - Plouvier, Martine (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: beauport

Belbuc, Belboch, Bialoboki. Über das Projekt zur Erforschung des Prämonstratenserstift - Rębkowski, Marian (Klasztor premonstratensów w Bialobokach. Archeologia i historia, 2015)
Keywords: białoboki

Belbuc, Belboch, Bialoboki. Wprowadzenie do badan klasztoru prem onstratensów - Rębkowski, Marian (Klasztor premonstratensów w Bialobokach. Archeologia i historia, 2015)
Keywords: białoboki

Klasztor premonstratensów w Białobokach: archeologia i historia - Rębkowski, Marian; Biermann, Felix (Instytut Archeologii i Etnologii Polskiej Akademii Nauk : Ośrodek Archeologii Średniowiecza Krajów Nadbałtyckich, 2015)
Das Prämonstratenserstift in Belbuck : Archäologie und Geschichte
OCLC: 911225361
Keywords: białoboki

Der Dom zu Havelberg und sein mittelalterlicher Lettner - Reichel, Antje (Verlag Janos Stekovics, 2015)
Keywords: havelberg

Devon's Torre Abbey: Faith, Politics and Grand Designs - Rhodes, Michael (The History Press, 2015)
Keywords: torre

Imagen religiosa e indumentaria en torno a 1500: las pinturas de Nuestra Señora de Brazacorta (Burgos) - Sanz, María Teresa López de Guereño (Boletín de la Asociación Española de Amigos de la Arqueología, 2015)
Imagen religiosa e indumentaria en torno a 1500: las pinturas de Nuestra Señora de Brazacorta (Burgos)
Keywords: brazacorta

Saint-Pierremont en Lorraine: une abbaye de chanoines réguliers et son pays aux XIIe et XIIIe siècles - Schleef, Yorick (Un "scriptorium" et son époque. Les chanoines de Beauport et la société bretonne au Moyen Âge, 2015)
Keywords: saint-pierremont

"... eine böse neuwe zeytung ... ": das Ende des Prämonstratenserinnenklosters Gommersheim - Schnabel, Berthold (Heimatjahrbuch Landkreis Alzey-Worms, 2015)
Keywords: gommersheim

Marienthal, St. Maria: Prämonstratenserinnenstift St. Mariental: Stadtteil Marienthal, Stadt und Verbandsgemeinde Rockenhausen, Donnersbergkreis - Schnabel, Berthold; Wenz, Martin; Untermann, Matthias (Pfälzisches Klosterlexikon : Handbuch der pfälzischen Klöster, Stifte und Kommenden, 2015)
Keywords: marienthal

Münsterdreisen, St. Saturnius: Frauengemeinschaft, später (Regular-)Kanonikerstift, dann Prämonstratenserabtei: Münsterhof, Gemeinde Dreisen, Verbandsgemeinde Göllheim, Donnersbergkreis - Schnabel, Berthold; Werling, Michael (Pfälzisches Klosterlexikon, 2015)
Keywords: münsterdreisen

Laval Dieu: Une abbaye prémontrée dans les Ardennes, 1128-1791 - Schrub, Bernard (CREHLOM, 2015)
Keywords: laval dieu

Die Abtei von Saint-Martin in Tournai im Spannungsfeld zwischen Cluny, Citeaux und Prémontré? Zur Konstruktion kollektiver Identität im Liber de restauratione Hermanns von Tournai - Sellner, Harald (Identität und Gemeinschaft: Vier Zugänge zu Eigengeschichten und Selbstbildern institutioneller Ordnungen, 2015)
Keywords: 📚 premonstratensian (general)

Abbaye Saint Nicolas de Septfontaines en Bassigny. Dix siècles d'histoire-Essai de chronologie - Selva, R. de (Actes officiels des 34e et 35e Colloques du Centre d'études et de recherches prémontrées : Sarthe, 2008, Lorraine 2009, 2015)
Keywords: septfontaines en bassigny

Komplexní obnova konventního kostela Narození Panny Marie v Želivě restaurování hlavního oltáře - Severa, Petr (Památky Vysočiny, 2015)
OCLC: 1224326282
Keywords: želiv

Bayham Abbey, East Sussex Historic Buildings Watching Brief - Shapland, M. (2015)
Keywords: bayham

Flora in Stein: Florale Motive im Bauschmuck im Kloster Jerichow - Telemann, Josefine (Lapidarium Jerichowense, 2015)
Keywords: jerichow

La commémoration des morts dans la liturgie de Prémontré: les trois obituaires de l'abbaye de Ninove. Quelques remarques à l'occasion de l'édition critique du texte - Van De Perre, Dirk (Actes officiels des 34e et 35e Colloques du Centre d'études et de recherches prémontrées : Sarthe, 2008, Lorraine 2009, 2015)
Keywords: ninove

Hermoesestraat 17 in Zennewijnen - Van Rooij, J.A.G. (DANS Data Station Archaeology, 2015)
Keywords: zennewijnen

Majetkový vývoj kláštera Louka u Znojma do husitských válek - Vohryzek, Stanislav (2015)
Cílem článku je podat přehled majetkového vývoje premonstrátského kláštera v Louce u Znojma od jeho založení roku 1190 knížetem Konrádem II. Otou do počátku husitských válek. Základním pramenem pro poznání vývoje klášterního majetku jsou listiny klášterního archivu. První část práce v chronologické řadě pojednává o založení kláštera a jednotlivých panovnických i šlechtických donacích. Velká pozornost je věnována zejména určení jednotlivých lokalit, které jsou zmiňovány v těchto listinách. Druhá část se zabývá vztahy kláštera ke kostelům, které mu byly inkorporovány již od počátku, nebo u nichž získal v průběhu času desátky či patronátní práva a inkorporace dosáhl později. Podán je zde i výčet sporů kláštera o tyto kostely a jejich desátky s jinými duchovními institucemi. Exkurz je věnován vztahu kláštera a města Znojma, např. problematice klášterních majetků, o které klášter přišel při vzniku města, způsobem jeho odškodnění, různým pozdějším vzájemným sporům, vlivu kláštera na ustanovování městského rychtáře apod.
Keywords: louka

Založení kláštera v Nové Ríši a otázka zakladatelských práv k nemu do válek husitských - Vohryzek, Stanislav (Casopis matice moravské, 2015)
[The Foundation of the Monastery in Nová Ríše and the Question of Founder Rights over It]
Keywords: nová říše

Voix et présence. Lettres historiées d'un missel du XIIIe siècle à l'usage de Notre-Dame de Belval (Charleville-Mézières, BM, ms. 243) - Voyer, Cécile (Le manuscrit, entre écriture et texte, 2015)
Keywords: belval

Von adeliger Gründerin, erfundenen Meisterinnen und bürgerlicher Liquidierung 1808: das Chorfrauenstift Nieder-Ilbenstadt - Wolf, Jürgen Rainer (Analecta Praemonstratensia, 2015)
Keywords: niederilbenstadt